Studi Literatur : Analisis Peranan Tingkat Pengetahuan Wanita Usia Subur Tentang Kanker Serviks Terhadap Tindakan Pap Smear - Naradha, I Made Krisna; Candra Rini Hasanah Putri (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Introduction: Cervical cancer is a type of malignant tumor characterized by the appearance of abnormal cells in the cervix. According to WHO data, Indonesia has the highest number of cervical cancer patients in the world. One of the efforts to reduce the high incidence of cervical cancer is early prevention. The purpose of this study was to determine the relationship between the level of knowledge of women of childbearing age about cervical cancer and the act of pap smear examination. Method: The research method used is a literature study and analyzed through the results of research that has been done before and has been published in the form of scientific journals and other official sources. Result: The literature review show that (100%) of the journals reviewed showed a sig value < 0,05. Conclusion: The result of the literature study research on journals that examine the relationship between the level of knowledge of women of childbearing age about cervical cancer with pap smear examination actions can be concluded that all journals mention there is a significant relationship between the level of knowledge of women of childbearing age about cervical cancer with pap smear examination actions.